PENGEMBANGAN BAHAN AJAR OPERASI BENTUK ALJABAR KELAS VII SEKOLAH MENENGAH PERTAMA (SMP) DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) - Kesumawati, Nila; Rohayah, Siti; Darmawijoyo, Darmawijoyo (Jurnal Dosen Universitas PGRI Palembang)
Abstract. This study aims to develop teaching material for algebra operations for grade of junior high school using the approach of Indonesian Realistic Mathematics Education and determine its potential effects on learning outcomes. This study uses the type of formative research methods development research. Step by step studies include preliminary stages (preparation and designing) and the formative stages of evaluation (self-evaluation, revision, one to one, experts review, revision, small group, revision, and field test, revision). Data was collected by walk through, documentation, and test competencies. The result validates the expert views that teaching material of algebra operations for seventh grade of junior high school is an valid and practical that can be used in fields trials. The trials of teaching materials were conducted in junior high school 6 of Sekayu, Musi Banyuasin at 7.1 by 30 students. Competency test result show that 77% of students achieved minimum qualifications in which 47% with excellent qualifications, 40% good qualified, 6,7% sufficient qualification, and 6,7% lesws qualifications. The results of students answer analysis show that students are able to understand the problem, determine the variables in a problem, and expressed in algebraic form. However, students are not careful when completing subtraction algebraic expression using parentheses.Â Keywords: algebra expression, PMRI, teaching materials.